# Math

Solve using substitution
3x - 9y = 3
6x - 3y = -24

Solve using elimination
y - 1/2x = 6
2x + 6y = 19

1. 👍 0
2. 👎 0
3. 👁 116
1. 3x - 9y = 3
6x - 3y = -24

from the first, divide by 3
x - 3y = 1
x = 3y+1

sub into the 2nd
6(3y+1) - 3y = -24
18y + 6 - 3y = -24
15y = -30
y = -2
then x = -6+1 = -5

for the 2nd system, multiply the 1st by -4
2x -4y = -24
2x + 6y = 19
subtract them
10y = 43
y = 43/10 = 4.3
into the 2nd:
2x + 6(4.3) = 19
2x = 19 - 25.8
2x = -6.8
x = -3.4

1. 👍 0
2. 👎 0
posted by Reiny
2. Eq1: 3x - 9y = 3
Eq2: 6x - 3y = -24

In Eq1, solve for X:
3x = 9y + 3
X = 3y+1

In Eq2, replace X with 3y+1:
6(3y+1) - 3y = -24
18y+6 - 3y = -24
15y = -30
Y = -2.

In Eq1, replace Y with-2:
3x-9*(-2) = 3
3x + 18 = 3
3x = -15
X = -5.

Solution set: (-5,-2).

Eq1: Y - X/2 = 6
Eq2: 2x + 6y = 19

Multiply Eq1 by 4 and add Eq2:
-2x + 4y = 24
+2x + 6y = 19
Sum: 10y = 43
Y = 4.3

In Eq1, replace Y with 4.3:

4.3 - 0.5x = 6
-0.5x = 1.7
X = -3.4

Solution set: (-3.4,4.3).

1. 👍 0
2. 👎 0
posted by Henry
3. Reiny, we meet again!! LOL! Oh well, we

1. 👍 0
2. 👎 0
posted by Henry

## Similar Questions

1. ### algebra

i need help with these problems (either a solution or how to plug them into a graphing calculator): 1) Solve by substitution or elimination 4/x + 1/y + 2/z = 4 2/x + 3/y - 1/z = 1 1/x + 1/y + 1/z = 4 2)Solve the system of

asked by Alyssa on April 5, 2011
2. ### Math

x=-y+3 5x-y=-2 Solve using Elimination I already solved the equation using Substitution, Graphing, and a table I just need a little more help on Elimination. I know that in Elimination they have to be in the same form so I put it

asked by M on January 20, 2015
3. ### Math Homework

Hello! I need help with these math questions, thanks! :) 1.) Solve the system by substitution. 5x + 2y = -17 x = 3y 2.) Solve the system by substitution. x/3 + y = 4/3 -x + 2y = 11 3.) Solve the system by elimination. 2x - 3y = 0

asked by Beni on December 7, 2013
4. ### Algebra 1

bobpursey, In this problem you helped me with earlier: Solve using any appropriate method. y = 2× - 5, y = ½× + 1 Substitution, substitute for y. 2×-5=½ × + 1 3/2 x=6 x=4 y= 2*4-5=3 How did you choose which method you were

asked by slomo on January 3, 2015
5. ### math

(Systems) how do I solve 5x+3y=2 and x+2y=6 using substition This is what I did X+2y=6 eq.1 5x+3y=2 eq.2 X=-3y/5 Sub(x=-3y/5) into eq.1 -3y/5 + 2y=6 7/5y=6 y=30/7 Sub(y=30/7) into eq.2 5x+3(30/7)=3 5x+90/7=3 5x=-69/7 x= -68/35 The

asked by Esther on March 1, 2017
6. ### Pre-Calculus

Solve the system of equations using matrices. Use Gaussian elimination with back-substitution. x + y + z = -5 x - y + 3z = -1 4x + y + z = -2 I really need help.. 1 1 1 -5 1 -1 3 -1 4 1 1 1 -2 I've done so many different methods

asked by Alexa on June 7, 2016
7. ### algebra2

solve the systems of equation: First : 4x-2y = 2 Second: y = -4x-7 Should i solve by using substitution, elimination or multiply then use elimination? Try adding them. Add up the left sides and the right sides (after rearranging

asked by ann on July 26, 2007
8. ### Algebra

Solve: 3x-2y=10 2x+3y=-2 Graph: Substitution: Elimination: Show Your work! (I can'tfigure out how to graph it and when i used substitution and elimination it came out with two different anwsers. I got (13/3.5,19/10.5) for

asked by Darryl on January 17, 2011
9. ### math

hOW can I solve this by elimination? I know how to solve by substitution but not elimination 3x – 2y = 0 9x + 8y = 7

asked by jess on November 2, 2017